PHYSICAL DEVELOPMENT OF TRAINING GROUP SHORT-DISTANCE RUNNER TRAINERS - Utayev Zafar (American Journals, 2023)
In this article, the experiences of the leading scientist (V.B.Papov) on the physical development of short-distance runners of the training group are studied. Model indicators for physical development and training of short-distance runners have been developed. Necessary recommendations on the admission of short-distance runners to training based on their anthropometric indicators are given. Pedagogical tests were organized and the results were discussed to determine the physical development of short-distance runners of the training group.
Keywords: Training, frequency, preparation, technique, sports exercise, result, modeling, pedagogical experience, anthropometric, comparison, planning, dynamics.